FOOD/DRUG AND DRUG/NUTRIENT INTERACTIONS: What You Should Know About Your Medications - Linda B. Bobroff; Ashley Lentz; R. Elaine Turner (EDIS)
Revised! FCS-8092, a 10-page fact sheet by Linda Bobroff, Ashley Lentz, and R. Elaine Turner, describes common food/drug and drug/nutrient, and how consumers can see the potential for interactions and learn to avoid them. Includes references. Published by the UF Department of Family Youth and Community Sciences, May 2009.